Informação, inovação e democratização: a transferência de conhecimento e o movimento associativo - González de Gomez, Maria Nélida (1992)
It is questioned a paradox of industrial capitalistic countries; when ever these societies increased their excedents and recourses of information, the actions and spaces of intersubjective communication decreases. In the dependent modernization societies, the communication-information "hiatus" is reinforced by new processes of dualization. In that situation, the professional’s categories have a role in the institucionalization of information and cultural patterns. In this context, it is studied the professional association of information ativities, and its possible participation in the reformulation of knowledge-information transfer’s chain.